Apoptosis-inducing effect of recombinant Caspase-3 expressed by constructed eukaryotic vector on gastric cancer cell line SGC7901 - Fu, Yuan-Gen (World J Gastroenterol, 2003)
AIM: To investigate the apoptosis-inducing effect of Caspases-3 expressed by constructed eukaryotic vector on gastric cancer cell line SGC7901. METHODS: PCR was employed to amplify the sequences of both small and large subunits of Caspases-3. Its products were separately cloned into the Sma I site of pBluescript KS(+) to generate both plasmids pBS/SS and pBS/LS. The small subunit fragment was excised from plasmid pBS/SS with BamH I and then inserted into the BamH I site of plasmid pBS/LS preceding that of the large subunit to yield plasmid pBS/Rev-Caspase-3. Rev-Caspase-3 cDNA was excised with Kpn I + Xba I and then subcloned into plasmid pcDNA3.1 (+) to construct Rev-Caspase-3 eukaryotic expression vector pcDNA/Rev-Caspase-3, which was used to transiently transfect SGC7901 cell line. Cell count, MTT assay and electron microscopy were used to confirm the antiproliferation and apoptosis-inducing effect of Rev-Caspase-3 expression on gastric cancer cells. RESULTS: Plasmid pBS/Rev-Caspase-3 and eukaryotic expression vector pcDNA/Rev-Caspase-3 were successfully constructed. SGC7901 cells were transiently transfected by either pcDNA/Rev-Caspase-3 or pcDNA3.1 (+) for 24, 48, 72, and 96 h respectively. Cell growth was measured by cell count and MTT assay. In cell count assay, the cell numbers were 1.8 × 10(6), 1.55 × 10(6), 2.0 × 10(6), and 3.1 × 10(6) in the experimental group and 2.5 × 10(6), 3.1 × 10(6), 4.0 × 10(6), and 5.7 × 10(6) in the control group at 24, 48, 72 and 96 h respectively. The growth of SGC7901 cells was suppressed by Rev-Caspase-3 in a time-dependent manner (P < 0.05). The results of MTT assay were similar to that of cell count (P < 0.05). The characteristics of apoptosis such as chromatin condensation, crescent formation and margination were seen and more obvious with time in the given-experimental period in the experimental group, but not easily observed in the control group. CONCLUSION: The expression of Rev-Caspase-3 by the constructed eukaryotic vector can significantly induce apoptosis of gastric cancer cell line SGC7901, which may exhibit a potential way in gastric cancer gene therapy.